Corporate governance and firm performance in Pakistan: The case of Karachi Stock Exchange (KSE)-30 - Qaiser Rafique, Yasser; Harry, Entebang; Shazali, Abu Mansor (Academic Journals Inc., 2011)
This paper examine the relationship between four important corporate governance mechanisms (board size, board composition, CEO/chairman duality and audit committee) and two firm performance measures (return on equity, ROE, and profit margin, PM), for a sample of 30 Pakistani listed firms between 2008 and 2009. The results provide evidence of a positive significant relationship between ROE and PM and three corporate governance mechanisms (board size, board composition and audit committee). The implication of this is that, the board size should be limited to a sizeable limit and board must be a right mixture of executive and non-executive directors. The study, however, could not provide a significant relationship between the two performance measures (ROE and PM) and CEO/Chairman duality. These results are consistent with prior empirical studies.